Preparation and Characterization of Multicomponent Crystal Piperine-Caffeine - Fitriani, Lili; Simbolon, Clara Alverina; Zaini, Erizal (Fakultas Farmasi Universitas Andalas, 2023)
Piperine (C17H19NO3) belongs to the alkaloid group mainly found in the Piperaceae family, especially in black pepper (Piper nigrum L.). Piperine is practically insoluble in water. This study aims to improve the solubility of piperine by preparing it into a multicomponent crystal using caffeine as a coformer. The formation of piperine-caffeine multicomponent was prepared by solvent evaporation and solvent drop grinding. Each sample was characterized using Powder X-ray diffraction (XRD), Differential Scanning Calorimetry (DSC), and FT-IR spectroscopy. The solubility test was carried out by sonication for 30 minutes at room temperature (30 â°C), and the dissolved piperine was analyzed by High-Performance Liquid Chromatography (HPLC) using methanol: water (80:20) as the mobile phase. This study shows a decrease in peak diffraction intensity on PXRD analysis and a reduction in endothermic peak on the DSC thermogram of multicomponent crystals. In the FTIR analysis, multicomponent crystals slightly shift, indicating the physical interaction. The multicomponent crystal of piperine-caffeine prepared by solvent evaporation method has an increase in solubility of 2.56 times, and the multicomponent crystal with solvent drop grinding method has an increase in solubility of 1.61 times, respectively. In conclusion, the multicomponent crystal piperineâ€“caffeine can enhance the solubility of piperine.